The relationship between knowledge and maternal attitudes regarding giving colostrum to newborns in the practice of febertri midwives Mendrofa subdistrict. Lahomi district. West Nias - Sumiatik, Sumiatik (Jurnal EduHealth, 2024)
Colostrum is the first fluid secreted by the breast glands. Colostrum is given early to babies and continuous breastfeeding can protect and be the best for babies because babies can avoid disease and have 10-17 times anti-immune substances than mature milk. The aim of this research is to determine the relationship between knowledge and maternal attitudes regarding giving colostrum to newborns at the practice of midwife Febertri Mendrofa, Kec. Lahomi District. West Nias. The design of this research is descriptive, namely with a cross sectional study approach. The population in this study was 29 people with a purposive sampling technique in accordance with. The research results showed that the majority of respondents, 17 people (59%) had good knowledge and 12 people (41%) had poor knowledge. The majority of respondents, 16 people (595), had a positive attitude and 13 people (45%) had a negative attitude. The conclusion of this research is that there is a positive r value of 0.02. From the significance test of the correlation coefficient p value (0.02 < 0.05), there is a relationship between knowledge and attitudes regarding giving colostrum to newborns at the Febertri Mendrofa Midwife Practice, Kec. Lahomi district. West Nias. It is recommended that this research can provide insight into knowledge that can increase mothers' knowledge about giving colostrum to newborn babies